Electron mobility distribution in FD-SOI MOSFETs using a NEGF-Poisson approach. (July 2022) - DehdashtiAkhavan, Nima; Antonio Umana-Membreno, Gilberto; Gu, Renjie; Antoszewski, Jarek; Faraone, Lorenzo; Cristoloveanu, Sorin
Highlights: Theoretical calculation of Mobility spectrum in DG-SOI MOSFETs. NEGF-Poisson solver with scattering to calculate mobility. Conductivity and mobility calculation using Kubo-Greenwood formalism. Identifying main subband components in the Silicon contributing to the mobility. Abstract: Modern electronic devices consist of several semiconductor layers where each layer exhibits unique carrier transport properties that can be represented by a unique mobility characteristic. To date, the mobility spectrum analysis technique is the main approach that has been developed and applied to the analysis of conductivity mechanisms of multi-carrier semiconductor structures and devices. Currently, there are no theoretical calculations of the mobility distribution in semiconductor structures or devices and specifically in MOSFET devices. In this article, we present a theoretical study of the electron mobility distribution in planar fully-depleted silicon-on-insulator (FD-SOI) transistors employing quantum mechanical modelling. The simulation results indicate that electronic transport in the 10 nm thick Si channel layer at room-temperature is due to two distinct and well-defined electron species for channel length varying from 50 nm to 200 nm. The two electron mobility distributions provide clear evidence of sub-band modulated transport in 10-nm thick Si planar FD-SOI MOSFETs that are associated with primed and non-primed valleys of silicon. The potential of the top gate electrode has been modulated, and thus only the top channel inversion-layer electron population transport parameters have been investigated employing self-consistent non-equilibrium Green's function (NEGF)–Poisson numerical calculations. The numerical framework presented can be used to interpret experimental results obtained by magnetic-field dependent geometrical magnetoresistance measurements and mobility spectrum analysis, and provides greater insight into electron mobility distributions in nanostructured FET devices.